Contribution to infection spread prevention in dental office - Anđelković Maja; Kostić Milena (Medicinski fakultet i Klinika za stomatologiju, Niš, 2023)
Introduction: Interventions in dental offices involve direct contact with the saliva and blood of patients, thus, dental staff is exposed to a constant risk of transmission of various infectious diseases Aim of the paper was to present the ways and means of spreading infection in dental offices, as well as measures to prevent it in order to protect the health of dental staff and patients. The risk of infection in healthcare institutions, especially in dental offices, is ever-present. Interventions in the mouth involve contact with the patient's saliva and blood, as well as with numerous pathogenic microorganisms that make up the patient's permanent or transient oral flora. The increase in the number of hepatitis B and hepatitis C patients, as well as those infected with HIV, indicates additional caution. The COVID-19 pandemic determined even more rigorous recommendations to prevent the spread of this infection. It is crucial that dental staff, bearing in mind the characteristics and ways of spreading the infection, undertake appropriate activities to prevent and control infectious diseases, thereby protecting themselves and their patients. Conclusion: Compliance with recommended infection control procedures is imperative for the entire dental staff.